Characterization of Invasive Neisseria meningitidis from Atlantic Canada, 2009 To 2013: With Special Reference to the Nonpolysaccharide Vaccine Targets (Pora, Factor H Binding Protein, Neisseria Heparin-Binding Antigen and Neisseria Adhesin A). Issue 6 (2015) - Tsang, Raymond SW; Law, Dennis KS; Gad, Rita R; Mailman, Tim; German, Gregory; Needle, Robert
Abstract : BACKGROUND: Serogroup B Neisseria meningitidis (MenB) has always been a major cause of invasive meningococcal disease (IMD) in Canada. With the successful implementation of a meningitis C conjugate vaccine, the majority of IMD in Canada is now caused by MenB. OBJECTIVE: To investigate IMD case isolates in Atlantic Canada from 2009 to 2013. Data were analyzed to determine the potential coverage of the newly licensed MenB vaccine. METHODS: Serogroup, serotype and serosubtype antigens were determined from IMD case isolates. Clonal analysis was performed using multilocus sequence typing. The protein-based vaccine antigen genes were sequenced and the predicted peptides were investigated. RESULTS: The majority of the IMD isolates were MenB (82.5%, 33 of 40) and, in particular, sequence type (ST)-154 B:4:P1.4 was responsible for 47.5% (19 of 40) of all IMD case isolates in Atlantic Canada. Isolates of this clone expressed the PorA antigen P1.4 and possessed the nhba genes encoding for Neisseria heparin-binding antigen peptide 2, which together matched exactly with two of the four components of the new four-component meningococcal B vaccine. Nineteen MenB isolates had two antigenic matches, another five MenB and one meningitis Y isolate had one antigenic match. This provided 75.8% (25 of 33) potential coverage for MenB, or a 62.5% (25 of 40) overall potential coverage for IMD. CONCLUSION: From 2009 to 2013, IMD in Atlantic Canada was mainly caused by MenB and, in particular, the B:4:P1.4 ST-154 clone, which accounted for 47.5% of all IMD case isolates. The new four-component meningococcal B vaccine appeared to offer adequate coverage against MenB in Atlantic Canada.